Il servizio idrico online Il portale SIT-SIRSI del Ministero delle Infrastrutture - Morenzetti, Ugo (GEOmedia, 2008)
The online water management service: the SIT-SIRSI portal for The Italian Ministry of Infrastructure The article introduces our readers to the SIT-SIRSI portal activated by the Italian Ministry of Infrastructure. The context is based onthe community directives dedicated to the european water resources protection and preservation. Specifically referred to the central and southern regions of Italy, which are considered at risk by the European Community, the portal also gained an important aknowledgement during the tenth italian ESRI Users Conference.